Bridge of Support: The Economic Impact of Foodbank WA - Koshy, Paul; Phillimore, John (Curtin University of Technology, 2008)
This paper quantifies the impact of Foodbank WA, a private not-for-profit organisation that provides a logistical and distributive interface - the bridge of support - between food producers with surplus or non-retailable foodstuff stocks and community agencies which access food products in large volumes. In 2007 this involved the collection and distribution of 1.5 million kilograms of food across Western Australia (WA) including regional centres. As a result these foodstuffs were not sent to landfill, at considerable savings to producers, and community agencies have been able to reduce the cost of sourcing food for their clients. The scale of Foodbank WA's operations means that each week approximately 8,300 households (or 1% of all households in WA) are provided with at least part of their food supply. The total economic impact of Foodbank WA's operations is AUD$18.4 million in a calendar year.